India Government Policies in Handling Gender-Based Violence against Women during the COVID-19 Pandemic: A Feminist Perspective - yoana septiani setiya ferisca; ningsih susilawati; ida bagus putu aditya; indra krishnamurti (IULI Publisher, 2023)
Abstract. India's entrenched patriarchal culture and practices result in gender inequalities that aredetrimental to women. The view that women are inferior to men results in women not having thesame opportunities as men, and the normalization of violence against women in the Indian society.The Covid-19 pandemic at the beginning of 2020 required India to implement quarantine and lockdown to prevent the spread of the Coronavirus. These quarantines and lockdowns lock women in thehome with perpetrators of violence and make it difficult to access assistance, leading to an increasein the number of domestic violence in India. The government's role is vital, especially at critical timeslike this, to overcome gender-based violence, especially domestic violence against women. This studyaims to analyze, through the lens of feminism theory in international relations, how the Indiangovernment deals with gender-based violence against women during the Covid-19 pandemic. Toanswer this question, the author will use a qualitative method by analyzing data and informationobtained from the mass media, journal articles, and various official documents. The findings of thisstudy are, the Indian government did not consider the issue of gender-based violence as essential atthat time. Even though the Indian government continues to run and open women-specific schemesduring the pandemic, but there are no new initiatives on a national scale; initiatives are only carriedout by a few states, which of course, only have an impact in specific areas. Funding for women'ssupport schemes is also reduced so that the amount of assistance and the quality that can be providedis limited and not maximized. This is due to the lack of participation of women in governance andpolicy making, so that the resulting policies do not target the needs of women. Keywords: India, Women, Gender-based Violence, Domestic Violence, Government Policies